PELATIHAN KONSTRUKSI ANGGARAN YANG EFEKTIF DAN EFISIEN BERBASIS METODE ABC DI PKBM AL KHODIJAH KOTA MALANG - Deni Nugroho Setyabudi; Heru Sofian (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2022)
Every organization is required to develop an activity-based financial system that is effective and efficient. Therefore, the financial performance of the organization must be based on the form of a budget that reflects these objectives. A budget that is able to reflect effectiveness and efficiency is the activity based costing (ABC method) budget method. Through this activity-based costing-based budgeting method, organizations can see and monitor the use of budgets and costs in accordance with the activities needed to carry out organizational performance. Activity-based budget construction training can provide assistance and benefits in the implementation, monitoring and evaluation of performance. Thus, all budget requirements and cost items can be tracked and their use can be accounted for. Activitybased budgeting also greatly facilitates rational and reliable decision-making so that in the end it can reflect an organizational management based on good corporate governance